The indigenous movement in Ecuador: resource access and Rafael Correa’s citizens’ revolution (2019)
The indigenous movement in Ecuador notoriously lost its political influence during Rafael Correa’s government, which is counterintuitive, as both actors – in theory – shared a similar political agenda. To explain this phenomenon, the extant academic literature has posed several hypotheses, all primarily based on the study of Ecuador’s political juncture. In an alternative, but complementary, manner, and based on the Resource Mobilization Theory (RMT), the main aim of this article is to analyze how the exchange relationship between resource types and resource access mechanisms of the Ecuadorian indigenous movement were affected under Rafael Correa’s administration. The results indicate that the exchange relationship between cooptation and appropriation employed by Correa’s regime altered the indigenous movement’s resource access during 2007–2017, resulting in the movement’s loss of influence and legitimacy within the Ecuadorian political arena. In addition, this article discusses the potential impact of resource access mechanisms on the empowerment and development of social movements; a relevant factor to understand their failure or success.